Genetic Markers of Hereditary Thrombophilia and Risk of Thrombotic Complications in Patients with Polycythemia Vera - DI Shikhbabaeva (Kliničeskaâ onkogematologiâ, 2017)
Background. Thrombotic complications are one of the main problems of polycythemia vera (PV) treatment. They significantly impair the quality of life of these patients and may lead to the lethal outcome. A thrombotic event often precedes the diagnosis of this hematological disease. The pathogenesis of thrombosis in myeloproliferative neoplasms, PV, in particular, is a complex one. Prescription of antiaggregants in the absence of thrombosis and anticoagulants after a thrombotic event requires special attention and development of corresponding recommendations. The prescription of anticoagulants is impossible without taking into account the risks of hemorrhagic complications, which are also typical for myeloproliferative neoplasms.